Left and right brain-oriented hemisity subjects show opposite behavioral preferences - Morton, Bruce E. (Frontiers in Physiology, 2012)
Introduction: Recently, three independent, intercorrelated biophysical measures have provided the first quantitative measures of a binary form of behavioral laterality called “Hemisity”, a term referring to inherent opposite right or left brain-oriented differences in thinking and behavioral styles. Crucially, the right or left brain-orientation of individuals assessed by these methods was later found to be essentially congruent with the thicker side of their ventral gyrus of the anterior cingulate cortex (vgACC) as revealed by a 3 minute MRI procedure. Laterality of this putative executive structural element has thus become the primary standard defining individual hemisity. Methods: Here, the behavior of 150 subjects, whose hemisity had been calibrated by MRI, was assessed using five MRI-calibrated preference questionnaires, two of which were new. Results: Right and left brain-oriented subjects selected opposite answers (p > 0.05) for 47 of the 107 “either-or”, forced choice type preference questionnaire items. Hemisity subtype preference differences were present in several areas. They were in: a. logical orientation, b. type of consciousness, c. fear level and sensitivity, d. social-professional orientation, and e. pair bonding-spousal dominance style. Conclusions: The right and left brain-oriented hemisity subtype subjects, sorted on the anatomical basis of upon which brain side their vgACC was thickest, showed numerous significant differences in their “either-or” type of behavioral preferences.